KUALITAS PELAYANAN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH KABUPATEN NATUNA - Vinni Helvionita; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Hospital is a regional government agency that provides public health services in each of their respective regions. One type of medical service given field in Natuna to public hospitals district is Outpatient Services which is one form of medical care that is simply the medical services provided to patients not in the form of hospitalization. The importance of quality of service sector in government and private agencies are lots impact good service to promote such an agency. The principal tasks Natuna District Hospital is carrying out measures to health by emphasizing healing, restoration carried out in harmony and integrated, with improved prevention and carrying out the references and experience high quality, affordable and appropriate professional standard hospital services. This study analyzed the quality of outpatient services in hospitals Natuna. Tjiptono theoretical concept in Hardiyansyah (2011: 40) There are six indicators to determine the quality of public services, namely: 1. Decision time service 2. Accuracy 3. Courtesy and hospitality services 4. Ease of getting care 5. Convenience in obtaining support services 6. Attribute servicing , This research is descriptive qualitative methods make use of more appropriate to examine the issues that require in-depth study. The purpose of this study is to identify and analyze the quality of outpatient services and to identify and analyze the factors that affect the quality of outpatient services in hospitals district Natuna. From the results of research and discussion is done about the quality of outpatient services in hospitals Natuna, it can be concluded outpatient services has set the standard operating procedures (SOP) of the hospital in Natuna regency, but not fully be undone optimally. It can be seen from several theories Tjiptono in Hardiyansyah (2011: 40) There are six indicators to determine the quality of service quality has not been done according to the needs of people who use services in hospitals Natuna. Quality of service is less than the maximum that could be used as a learning organization is an organization with all powers, jointly and continuously transforms itself to be able to collect, manage funds using knowledge for success in an organization. To the knowledge of those who want to learn to know the state of an organization both internally and externally to seek information through surveys and pay attention to deficiencies complained of by the community, employment is needed to create the organization's progress with the achievement of quality services.Keywords : Quality of Outpatient Services, Health Services, Hospital